2020
DOI: 10.1152/ajplung.00087.2019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fibroblast migration dynamics in idiopathic pulmonary fibrosis using image-based scaffolds of the lung extracellular matrix

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by a profound remodeling of the collagen in the extracellular matrix (ECM), where the fibers become both denser and more highly aligned. However, it is unknown how this reconfiguration of the collagen matrix affects disease progression. Here, we investigate the role of specific alterations in collagen fiber organization on cell migration dynamics by using biomimetic image-based collagen scaffolds representing normal and fibrotic lung, where the designs are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…This treatment should result in further spreading and polarization as ROCK itself enhances contraction. To quantify the elongation, we measured the angle of the cells relative to the fiber axis, where lower angles correspond to increased alignment [ 61 ]. As we found the largest differences in motility, cell shape, and cytoskeleton expression/alignment for cells on the normal and high-grade models, we chose these scaffolds for this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This treatment should result in further spreading and polarization as ROCK itself enhances contraction. To quantify the elongation, we measured the angle of the cells relative to the fiber axis, where lower angles correspond to increased alignment [ 61 ]. As we found the largest differences in motility, cell shape, and cytoskeleton expression/alignment for cells on the normal and high-grade models, we chose these scaffolds for this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…78,79 The importance of mechanical and structural properties of the ECM is well documented in the literature, with ECM stiffness and alignment key regulators of cellular behaviors involved in fibrosis, such as fibroblast alignment, migration, and proliferation. 22,80 Our study reveals changes in both ECM structure and mechanics in fibrosis, highlighting the need to study the role of therapeutics on collagen organization. Further, we must account for differences in collagen organization between tissue systems, especially as we aim to alleviate the deleterious impacts of fibrosis in DMD in the diaphragm muscle.…”
Section: Our Findings Implicate Changes In Ecm Structure and Mechanics On The Mechanical Properties Of Diaphragm Muscle As Dmd Progressesmentioning
confidence: 90%
“…[18][19][20][21] Beyond skeletal muscle, changes in collagen organization with fibrosis are implicated in additional tissue systems. Increased collagen fiber alignment is reported in pulmonary fibrosis 22 and increased collagen fiber straightness is reported in cancerous pancreatic tissue. 23 Changes in collagen organization, such as collagen fiber direction, alignment, and straightness, remain unknown in mdx diaphragm muscle, but are needed to understand how and why diaphragm muscle mechanics change during the progression of DMD.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of such cell positioning within fibrotic tissue were recently investigated by the Campagnola group. By tracking individual cells migrating on microfabricated three-dimensional collagen scaffolds, Tisler et al demonstrated that biomechanical features of collagen stroma affected by idiopathic pulmonary fibrosis greatly enhance cell polarity and facilitate directional cell movement along stiff and aligned collagen bundles [ 116 ]. It is tempting to speculate that contractile forces generated by myofibroblasts or other cell types in response to proinflammatory cytokines prestress and stiffen collagen fibers, and such mechanical gradients quickly propagate through tissue, attracting single cells and cell clusters to the fibrotic lesions [ 117 , 118 , 119 ].…”
Section: Tissue Stiffness—a Driver Of Inflammationmentioning
confidence: 99%